Socioeconomic and permanence conditions in Dentistry students, University San Gregorio de Portoviejo - Alvarado Roldán, Saul Vicente (2024)
Worldwide, student retention is an important factor in generating strategies that contribute to reducing the dropout rate and guaranteeing the successful completion of the students' academic processes. The research work aims to: Analyze the socioeconomic conditions and the permanence of students in the Dentistry career of the San Gregorio de Portoviejo University. The research was directed with a positivist approach and used the non-experimental correlational quantitative method, considering a sample of 292 students, to whom a virtual survey was applied using Google Forms and a questionnaire with a Likert scale. For data analysis, version 25.0 of the IBM SPSS v25 computer statistical software was used; (Statistical Package for Social Sciences/Statistical Package for Social Sciences); According to the descriptive and inferential statistical procedure, it is determined that the correlation is significant at a bilateral level of 0.01, there being a positive relationship between socioeconomic conditions and permanence.